Association between sectorial retinal nerve fiber layer thickness with anatomical variables of Lamina Cribrosa- A comparative study - Saba Naz, Ayesha; Qamar , Aisha; Surti , Ambreen; Mahar , Yasmeen (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective: To compare sectorial retinal nerve fiber layer thickness (RNFLT) with anterior Lamina Cribrosa depth (ALCD) and Lamina Cribrosa thickness (LCT) in primary open-angle glaucoma (POAG) cases and healthy age-matched controls Methods: This case-control study was conducted at Al-Ain Eye Institute, Karachi from November 2018 till February 2019. Senior ophthalmologist recruited 57 POAG cases and 46 age-matched healthy controls. Calculation of intraocular pressure (IOP) and open angle carried out using Goldmann tonometry and Slit-lamp biomicroscopy with stereoscopic ophthalmoscopy respectively. Extremely precise spectral domain ocular coherence tomography with enhanced depth imaging (EDI-OCT) utilized to determine ALCD, LCT and RNFLT. Results: RNFLT in various sectorial regions displayed statistically significant results (p-value of 0.001) when compared with controls. Superior retinal sector revealed the highest ranges of thickness (75.50 ± 9.64 µm), while thin retina was observed in global measurements (48.40 ± 0.84 µm). Enhanced ALCD was seen (545.50 ± 3.53 µm) among 15 POAG cases. Least thickness of LCT documented in the four POAG cases in inferior retinal sector (204.57 ± 79.04 µm). Conclusion: Assessments of RNFLT, ALCD and LCT provides valuable knowledge that can be utilized for the management and predicting the course and prognosis of POAG.